ChemInform Abstract: Practical Methods for the Synthesis of Trifluoromethylated Alkynes: Oxidative Trifluoromethylation of Copper Acetylides and Alkynes. Issue 49 (9th December 2014) - Tresse, Cedric; Guissart, Celine; Schweizer, Stephane; Bouhoute, Yassine; Chany, Anne‐Caroline; Goddard, Mary‐Lorene; Blanchard, Nicolas; Evano, Gwilherm
Abstract Two complementary methods for the preparation of trifluoromethylated alkynes are presented and compared.